Psychometric evaluation of the perceived access to health care questionnaire - Sara-Sadat H; Reza Negarandeh; Farzaneh Delavar; Leila Janani (BMC, 2021)
Abstract Background and objective Access to health care is a universal concern. Therefore, this study was conducted to develop a questionnaire to assess the Perceived Access to Health care based on Penchansky and Thomas's definition of access and the assessment of its psychometric properties. Method The initial questionnaire contains 31 items developed based on a deductive approach with an extensive review of the related literature. Content validity, face validity, construct validity, internal consistency, and instrument reliability were further examined. Data analysis was conducted using SPSS software version 24, R software version 4, and lavaan package. Results The initial questionnaire was examined using qualitative content validity, and the necessary modifications were applied to each item. The content validity ratio (CVR) was approved in 30 items with a value greater than 0.78, and one item with a CVR value lower than 0.78 was removed. In the case of the content validity index (CVI), 29 items were approved with a CVI value of greater than 0.79, and one item with a CVI value between 0.70 and 0.79 was revised. In qualitative face validity, all items were approved by a panel of experts and the participants. All 30 items with an impact score index higher than 1.5 were approved for the next steps. The confirmatory factor analysis results showed that the six-factor model of access to health care has an appropriate fit. Cronbach's alpha coefficient for the questionnaire was calculated 0.86. The value of Cronbach's alpha for the dimensions of availability, accessibility, affordability, accommodation, acceptability, and awareness were 0.61, 0.76, 0.66, 0.60, 0.80, and 0.76, respectively. The Intraclass Correlation Index (ICC) value for reliability (test-retest) of the whole instrument was calculated 0.94 using the two-way mixed absolute agreement method. Conclusion The success of health programs depends on eliminating barriers to access to provided health care services. One of the most critical barriers to understanding access is a perception of limited access. This questionnaire might be used further to understand perceived health care access in different global contexts.